Наукова діяльність українських вчених-емігрантів в міжвоєнний період: народницько-демократичний напрямок - Івасечко, Ольга (Видавництво Національного університету "Львівська політехніка", 2009)
In the article is considered the activity of Ukrainian emigrants center in the between – war period. Espessially attention is considered of representatives of the new – peoples trend of Ukrainian political thought: R. Lasthenko, S. Sheluhin, O. Mycuk, O. Salikovskyj. This article also is devoted to the analyses their to teach school and scientific activity.
Keywords: of Ukrainian scientific emigrants; the scientific center; of the scientific and teacher activity; the peoples – democratic trend